Community Perception and Dependence on Medicinal Plants Through the Role of Women in Skouw Yambe Village, Jayapura City, Papua - Beatrix Irene S Wanma; Iriani Ira Bukorpioper (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Papuans (Papua and West Papua Provinces) most of their lives depend on nature, including the community of Skouw Yambe Village, Muara Tami District, Jayapura City, which is very dependent on the surrounding natural resources, such as the use of plants as medicinal plants, food sources. as well as the completeness of traditional parties and rituals, besides that the people's livelihood is dominated by farmers and fishermen. The purpose of the study was to determine the perception and level of community dependence on medicinal plants in Skouw Yambe Village, Muara Tami District, Jayapura City, Papua. The method used in collecting research data is by interviewing and surveying the availability of medicinal plants and in the yard of houses and forests around the village by taking coordinates and giving status of availability of medicinal plants and giving a score or distribution of gravel based on the level of knowledge and personal experience (Pebble Distribution Method). /PDM). The results of the study found 31 types of traditional medicinal plants used by the people of Skouw Yambe Village, with sufficient availability around the village and the coast. Based on the gravel distribution method, it shows that the public perception of medicinal plants is still good. In general, the people of Skouw Yambe Village still use traditional medicinal plants and this knowledge is passed on to the next generation.